2021
DOI: 10.1128/msystems.00643-21
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Protein Interaction Analysis of SARS-CoV-2 5′ and 3′ Untranslated Regions Reveals a Role of Lysosome-Associated Membrane Protein-2a during Viral Infection

Abstract: Replication of a positive-strand RNA virus involves an RNA-protein complex consisting of viral genomic RNA, host RNA(s), virus-encoded proteins, and host proteins. Dissecting out individual components of the replication complex will help decode the mechanism of viral replication. 5′ and 3′ UTRs in positive-strand RNA viruses play essential regulatory roles in virus replication.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 59 publications
0
40
0
Order By: Relevance
“…RNA - protein interaction detection assay (RaPID assay) involves biotinylation of IRES interacting proteins, followed by their identification by liquid chromatography with tandem mass spectroscopy (LC-MS-MS) (28). RaPID assay was optimized in our laboratory (29). 87 nucleotides of the g1-HEV genome (Genbank ID: AF444002.1) corresponding to the IRESl region was cloned into the pRMB vector between the BirA ligase binding stem-loop (RMB-SLI, RMB-SLII) sequences (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…RNA - protein interaction detection assay (RaPID assay) involves biotinylation of IRES interacting proteins, followed by their identification by liquid chromatography with tandem mass spectroscopy (LC-MS-MS) (28). RaPID assay was optimized in our laboratory (29). 87 nucleotides of the g1-HEV genome (Genbank ID: AF444002.1) corresponding to the IRESl region was cloned into the pRMB vector between the BirA ligase binding stem-loop (RMB-SLI, RMB-SLII) sequences (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…43 and 8 host proteins identified as interaction partners of the HEV-IRESl RNA by RaPID and Y3H assay, respectively, were clubbed and imported to Cytoscape to generate the RNA-Protein-Protein interaction (RPPI) network, as described earlier (29). Analysis of the different network characteristics revealed that the HEV IRESl-RPPI network contained 51 nodes and 74 edges, the average node degree being 3.36.…”
Section: Identification Of Host Proteins That Interact With the Hev I...mentioning
confidence: 99%
See 1 more Smart Citation
“…Viruses can mimic the host’s mRNAs, which contains 5’ cap, 3’ polyadenylated tail, and untranslated regions (UTRs) on the 5’ and 3’ ends to take advantage of the host’s translational machinery ( 46 , 58 60 ). The 5’ and 3’ UTRs in the genome RNA play essential regulatory roles in virus replication, viral gRNA stability, host immunoregulation, and viral genome encapsulation ( 61 ). The SARS-CoV-2 genome has an m7G-cap structure, m7GpppA1, on the genome 5’ end, and a ~30-60-nt-long (47nts in median length) poly(A) tail on the 3’end for viral genome stability and preventing cellular exoribonuclease digestion ( 16 , 62 , 63 ).…”
Section: Proteins Encoded By Coronavirus Genomementioning
confidence: 99%
“…Another study investigated the interaction between 5′ and 3′ UTR of SARS-CoV-2 RNA and host proteins, revealing an enriched expression of proteins involved in RNA metabolism and translation initiation [ 134 ]. The study also identified Lysosome-associated membrane protein-2a (Lamp2a) as one of the 5′-UTR interacting proteins.…”
Section: Introductionmentioning
confidence: 99%